Volume 1A: Codes and Standards 2017
DOI: 10.1115/pvp2017-66097
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue With Hold Times Simulating NPP Normal Operation Results for Stainless Steel Grades 304L and 347

Abstract: The cyclic behavior and endurance of austenitic stainless steels tested under NPP-relevant laboratory conditions has been studied. It had been earlier shown that long intervals between fatigue transients can affect the fatigue performance in stainless steels that are generally used in NPP primary piping. If this can be confirmed, then the transferability between laboratory results, design curves and the fatigue behavior of NPP components during plant operation shall be addressed. In addition to coolant water e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…For tests in air, holds were added at 6000 cycle intervals starting from the 6000th cycle for strain range 0.3% and 1000 cycle intervals starting from the 1000th cycle for 0.6%. Preliminary analysis including Phase II tests ( [40,42], confirmed in Section 3.1.3) suggested that there was no observable effect of hold times for the tested conditions, although beneficial effects of hold time on fatigue life have been reported by the AdFaM (Advanced Fatigue Methodologies) project [13].…”
Section: Sub-programme On Hold Timesmentioning
confidence: 94%
See 4 more Smart Citations
“…For tests in air, holds were added at 6000 cycle intervals starting from the 6000th cycle for strain range 0.3% and 1000 cycle intervals starting from the 1000th cycle for 0.6%. Preliminary analysis including Phase II tests ( [40,42], confirmed in Section 3.1.3) suggested that there was no observable effect of hold times for the tested conditions, although beneficial effects of hold time on fatigue life have been reported by the AdFaM (Advanced Fatigue Methodologies) project [13].…”
Section: Sub-programme On Hold Timesmentioning
confidence: 94%
“…It also became apparent that applying hold times during some cycles in this study did not have a major effect on fatigue life. However, significant effects of hold times on fatigue life were reported in a different study [13]. To investigate whether differences in the application of holds led to these differences, a limited sub-programme on hold time tests was started (Section 3.3).…”
Section: Test Programmementioning
confidence: 99%
See 3 more Smart Citations